Whole-genome sequencing and analysis of Nocardia veterana isolates from keratitis patients - Veena Radhakrishnan; Lalitha Prajna; Bharanidharan Devarajan; Jeyaraman Jeyakanthan (Molecular Genetics and Genomics, 2026)

Deciphering the Effect of Functional Diet Containing Single and Multiple Strain Probiotic, on the Growth, Gut Histology and Microbiome Signatures in the Pacific White Leg Shrimp (Penaeus vannamei) - Natarajan Lalitha; Kondusamy Ambasankar; Sivaramakrishnan Thirugnanamurthy; Sherly Tomy; Panjan Nathamuni Suganya; Ashok Kumar Jangam (Current Microbiology, 2026)

Foliage to fiber: decoding the nutritional efficiency and assimilation of different hosts on growth and reproduction of Samia ricini (Donovan) (Lepidoptera: Saturniidae) - Lalitha Natarajan; Hridya Hemachandran; Arunima Nath; Lopamudra Guha; Kartik Neog (International Journal of Tropical Insect Science, 2026)

Enhancing machine learning workloads using optimized cloud-edge computing architectures with service function chaining - Shaik Sufia; Lalitha Kumari Pappala (Swarm and Evolutionary Computation, 2026)

Soil Property Prediction with Vis-NIR Spectroscopy in Different Depths: Testing the Robustness of Topsoil-Derived Models - K. Palani Renuka; S. Dharumarajan; M. Lalitha; R. Vasundhara; B. Kalaiselvi; A. Sathish (Journal of the Indian Society of Remote Sensing, 2026)

Exploring the Potential Herbicidal Activity of Actinomycetes Isolated from Western Ghats Soil, India - C. V. Babu; B. N. Ramesh; P. Bhavani; B. S. Lalitha (Indian Journal of Microbiology, 2026)

Integrative network and structural analysis of Pinus derived phytosterols in diabetes associated pathways - P. Roshan Ali; Gutti Krishna Sri; Gojuvaka Sravanthi; Kavirayani Naga Lakshmi Shivani; Rajinikanth Sagapola; Kalasani Divya; V. V. Rajesham; Mitta Raghavendra; Dyvapu Lalitha Bhaskarini (In Silico Pharmacology, 2026)

Evaluation of Eupatorium perfoliatum loaded chitosan nanocarriers in silico, in vitro and in vivo for anti-inflammatory, antipyretic and analgesic potential - Sorimuthu Revathi; Nibedita Dey; Subramanian Thangaleela; Kubera Kumar; Anita Roy; Lalitha Gnanasekaran; D. Shanmugapriya; Sajad Ali; Ashley George Thomas; Thanigaivel Sundaram (Food Bioscience, 2026)

A quercetin derivative from Sarcostemma brevistigma mitigates silica-induced pulmonary injury via regulation of TLR4/NF-κB and Nrf2 signaling pathways - Peramaiyan Rajendran; Ramya Sekar; Abdullah Alzahrani; Rajkapoor Balasubramanian; Emad A. Ahmed; Gamal M. Behket; Rebai Ben Ammar; Lalitha Keddal Govindaram (Toxicon, 2026)

Microplastics and antimicrobial resistance: A growing threat to aquatic health, food safety, and the one health framework - Surya Narayanan S.; Lalitha Gnanasekaran; Saranya Vinayagam; Dai-Viet N. Vo; Thanigaivel Sundaram (Environmental Research, 2026)

Retraction notice to “Support based metal incorporated layered nanomaterials for photocatalytic degradation of organic pollutants” [Environ. Res. 260 (2024) 119481] - Awais Ahmad; Arsh e Noor; Aneela Anwar; Saadat Majeed; Safia Khan; Zaib Ul Nisa; Shafaqat Ali; Lalitha Gnanasekaran; Saravanan Rajendran; Hu Li (Environmental Research, 2026)

Nano catalyzed green synthesis of chalcone derivatives and its anti-oxidant and anti-lung cancer potential validated through in vitro experimentals, in silico quantum chemical, molecular docking and simulation studies - P. Vadivel; C. Thirumurugan; R. Thirumalaisamy; A. Lalitha (In Silico Pharmacology, 2026)

The Role of Functional Feed in Modulating Fish Gut Microbiome to Enhance Resistance Against Aquaculture Pathogens - Eswar Marcharla; A Vishnuprasadh; Lalitha Gnanasekaran; Saranya Vinayagam; Thanigaivel Sundaram; Swamynathan Ganesan (Probiotics and Antimicrobial Proteins, 2026)

Structure-based computational investigation of potential TarA inhibitors in Staphylococcus aureus - Boggarapu Ganesh; Lalitha Guruprasad (Molecular Diversity, 2026)

Facile engineering of reduced graphene oxide-anchored nickel selenide and molybdenum selenide nanocomposite for dual functionality in seawater electrolysis and supercapacitor applications - Paranthaman Vijayakumar; Sakthivel Kumaravel; S. Swathi; Vasudeva Reddy Minnam Reddy; Lalitha Gnanasekaran; Woo Kyoung Kim; Prajindra Sankar Krishnan; Tiong Sieh kiong (Fuel, 2026)

Design of inhibitors to Klebsiella pneumoniae aspartate semialdehyde dehydrogenase towards hospital-acquired infections - Adrija Banerjee; Gatta K. R. S. Naresh; Lalitha Guruprasad (Molecular Diversity, 2026)

Evaluating the ability of in silico identified hit compounds to bind Staphylococcus aureus LcpASA using steered molecular dynamics simulations - Boggarapu Ganesh; Adrija Banerjee; Lalitha Guruprasad (Molecular Diversity, 2026)

Prevalence and comparative analysis of Y chromosome microdeletions in recurrent pregnancy loss - M. L. N. Deepika; Avvari Srilekha; C. Lalitha Pavani; Aryan Gupta; Ridah Nazneen; B. Vijaya Lakshmi (Journal of Applied Genetics, 2026)

Comparison of precipitation, mechanochemical and pyrolytic methods for the synthesis of zinc oxide nanoparticles based on photocatalytic degradation - Anjali Mangat; Archana Somasekharan Nair; Aswathy Lalitha Balachandran; Anoop Somasekharan Nair (Next Research, 2026)

Correction to: miR Cluster 143/145 Directly Targets Nrl and Regulates Rod Photoreceptor Development - Sreekumaran Sreekanth; Vazhanthodi A. Rasheed; Lalitha Soundararajan; Jayesh Antony; Minakshi Saikia; Krishnankutty Chandrika Sivakumar; Ani V. Das (Molecular Neurobiology, 2026)

Retraction notice to ‘Environmental fate of aquatic pollutants and their mitigation by phycoremediation for the clean and sustainable environment: A review’ [Environ. Res. 240-Part 1 (2024) 117460] - S. Thanigaivel; Saranya Vinayagam; Lalitha Gnanasekaran; R. Suresh; Matias Soto-Moscoso; Wei-Hsin Chen (Environmental Research, 2025)

Mapping the spatial variability of soil organic carbon stocks in the South-Eastern Ghats region of India for ecosystem sustainability - R. Srinivasan; S. Amar Suputhra; M. Lalitha; V. Kasthuri Thilagam; Surabhi Hota; V. Ramamurthy (Tropical Ecology, 2025)

Emerging targets and translational challenges in treating paclitaxel-induced peripheral neuropathy - Sivadas Swathi Krishna; Nandana Shaji; Nandana V. Kumar; Aiswarya Das; Sabitha Mangalath; Lalitha Biswas; Keechilat Pavithran (Molecular Biology Reports, 2025)

Prioritization of candidate genes regulating the dwarfness in rice by integration of whole-genome and transcriptome analyses - Gunasekaran Ariharasutharsan; Adhimoolam Karthikeyan; Seshadri Geetha; Muthurajan Raveendran; Ravi Lalitha; Latha Ananda-Lekshmi; Manoharan Akilan; Dhanalakshmi Veeraraj Sushmitharaj; Manickam Dhasarathan; Ramasamy Saraswathi; Paramasivam Arunachalam (Functional & Integrative Genomics, 2025)

A multi-model deep learning approach for human emotion recognition - Lalitha Arumugam; Samydurai Arumugam; Pabitha Chidambaram; Kumaresan Govindasamy (Cognitive Neurodynamics, 2025)

Harnessing bacteriophage therapy as a sustainable solution for pathogen control in aquaculture - Vishnuprasadh A.; Saranya Vinayagam; Lalitha Gnanasekran; Thanigaivel Sundaram (Aquaculture International, 2025)

Fermented fish silage-based cost-effective farm made feed as an alternate to conventional formulated feed for Genetically Improved Farmed Tilapia (Oreochromis niloticus): effects on growth performance, feed utilization, whole-body composition, and economic efficiency - Oimps Lunghar; Kondusamy Ambasankar; Sivaramakrishnan Thirugnanamurthy; Natarajan Lalitha; Mohamed Saquib Naveed (Aquaculture International, 2025)

Black gram husk-derived carbon dots: characterization and catalytic dye reduction activities - N. S. Karthikeyan; B. Shanthi; R. Suresh; C. Ravichandran; B. Venkatachalapathy; K. Saravanan; Lalitha Gnanasekaran; Matias Soto-Moscoso (Clean Technologies and Environmental Policy, 2025)

Effect of dietary supplementation of Lactiplantibacillus plantarum probiotics as functional feed additive in Pacific white shrimp (Peneaus vannamei) - Natarajan Lalitha; Kondusamy Ambasankar; Sivaramakrishnan Thirugnanamurthy; Sherly Tomy; Panjan Nathamuni Suganya; Ramalingam Ananda Raja; Sujeet Kumar; Raman Nanthini; Oimps Lunghar (Aquaculture International, 2025)

Prediction of soil organic carbon stock along layers and profiles using Vis-NIR laboratory spectroscopy - S. Dharumarajan; C. Gomez; C.G. Kusuma; R. Vasundhara; B. Kalaiselvi; M. Lalitha; R. Hegde (CATENA, 2025)

Preliminary evaluation of biofuel production potentials for Southern Africa's encroacher and invasive bush biomass - Charles Rashama; Sajna Kuttuvan Valappil; Lalitha Gottumukkala; Uasora Katjouanga; Piotr Dobkowski; Johannes Shiwombolo; Hilma Namwandi; Bruce Bewer; Ben Mapani; Dan Hayes; David Wakefield (Bioresource Technology Reports, 2025)

Prediction and mapping of soil organic carbon stock via large datasets coupled with pedotransfer functions - Subramanian Dharumarajan; Kabindra Adhikari; Ranabir Chakraborty; Beeman Kalaiselvi; Ramakrishnappa Vasundhara; Manickam Lalitha; Rajendra Hegde; Hittangi Prakash; Sreekumar Parvathy; C. G. Kusuma; Ayyappa Sathish; N. L. Rajesh; et al. (Earth Science Informatics, 2025)

AI-driven plant health monitoring: evaluating the WRLSB-HPS algorithm for leaf disease classification - Kumar P; Hannah Lalitha; D. Jeya Priya; Bala Subramanian C (Earth Science Informatics, 2025)

Quantifying suitability of transit-oriented development in Indian cities - Lalitha Sree Chintakayala; C. S. R. K. Prasad (Innovative Infrastructure Solutions, 2025)

Ericulture host plants as carbon sinks: understanding the sustainable carbon sequestration potential - Hridya Hemachandran; Lalitha Natarajan; Arunima Nath; Lopamudra Guha; Sankari Mohan; Kartik Neog (Vegetos, 2025)

Role of micro- and nano-plastics in altering biogeochemical cycles - Nguyễn Hoàng Ly; Lalitha Gnanasekaran; Tejraj M. Aminabhavi; Yasser Vasseghian; Sang-Woo Joo (Current Opinion in Environmental Science & Health, 2025)

Degradative removal of diclofenac from wastewater - Statistical and analytical approaches to understand degradation pathways - Hiba Sadat; Nadia Guettai; Mohammed Berkani; Danen Appasamy; Christophe Douez; Lalitha Gnanasekaran; Tejraj M. Aminabhavi; Yasser Vasseghian; Yassine Kadmi (Journal of Environmental Management, 2025)

Cocooning with Cassava: Exploring the commercial rearing and seed production potential of Samia ricini Donovan on different Cassava varieties - Lalitha Natarajan; Hridya Hemachandran; Ramen Bhuyan; Hemanta Bordoloi; P. S. Sivakumar; Prabhat Borpuzari (International Journal of Tropical Insect Science, 2025)

Food Security Based Marine Life Ecosystem for Polar Region Conditioning: Remote Sensing Analysis with Machine Learning Model - Ganduri Srikanth; Divya Nimma; R. V. S. Lalitha; Pradeep Jangir; N. V. Siva Kumari; Arpita (Remote Sensing in Earth Systems Sciences, 2025)

Retraction notice to “Highly operative NiO/ZnO nanocomposites for photocatalytic removal of azo dye”[Chemosphere 308 (2022) 136528] - Lalitha Gnanasekaran; Wei-Hsin Chen; Matias Soto-Moscoso (Chemosphere, 2025)

Retraction notice to “Modified poly(vinylidene fluoride) nanomembranes for dye removal from water – A review” [Chemosphere 322 (2023) 138152] - R. Suresh; Saravanan Rajendran; Lalitha Gnanasekaran; Pau Loke Show; Wei-Hsin Chen; Matias Soto-Moscoso (Chemosphere, 2025)

Retraction notice to Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review [FUEL][340][2023][127399] - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2025)

Unveiling halophilic microbial communities in calcite fossil sedimentary rocks and their implications for biomineralization - Balachandar Chinnappa; Balaji Thirupathi; Thanigaivel Sundaram; Yimtar L. Pongen; Saranya Vinayagam; Lalitha Gnanasekaran; Vishnu D. Rajput; Thirumurugan Durairaj (Applied Soil Ecology, 2025)

Human bocavirus infections in paediatric patients in a tertiary care hospital in Kerala, India - B. Aneesh; Swapna K. Pillai; P. S. Chippy; Megha Chandran; Arun V. Jose; Lalitha Kailas; M. Neziya; S. Aswathyraj; E. Sreekumar (Archives of Virology, 2025)

Chiral plasmonic Au@Pt nanoparticles for detection of H2O2 and Hg2+ and enantiomeric differentiation - The Anh Quang; Thi My Cam Tran; Tejraj M. Aminabhavi; Lalitha Gnanasekaran; Yasser Vasseghian; Sang-Woo Joo (Journal of Environmental Management, 2025)

Between choice and sustainability: Navigating menstrual waste management in India through feminist political ecology and ecological modernization - By Lalitha Shanmugasundaram; Aman Luthra (Journal of Cleaner Production, 2024)

Photocatalytic degradation of organophosphorus pesticide (terbufos) in aqueous solutions using 3D-printed TaSe2/g-C3N4 nanocomposites - Tan Phat Dao; Thi Huong Vu; Van Duc Bui; Lalitha Gnanasekaran; Tejraj M. Aminabhavi; Yasser Vasseghian; Sang-Woo Joo (Chemical Engineering Journal, 2024)

Retraction notice to “Crude oil biodegradation aided by biosurfactants from Pseudozyma sp. NII 08165 or its culture broth” [Bioresource Technol. 191 (2015) 133–139] - Kuttuvan Valappil Sajna; Rajeev Kumar Sukumaran; Lalitha Devi Gottumukkala; Ashok Pandey (Bioresource Technology, 2024)

Unravelling role of crocin for the treatment of Alzheimer’s and Parkinson’s disease: sojourn from food to nanomedicine - Harmanpreet Kaur; Bushra Bashir; Amandeep Kaur; Navneet Singh; Sukriti Vishwas; Puneet Kumar; Harish Dureja; Motamarri Venkata Naga Lalitha Chaitanya; Thakur Gurjeet Singh; Gaurav Gupta; Aftab Alam; Francisco Veiga; et al. (Phytochemistry Reviews, 2024)

RETRACTED: Support based metal incorporated layered nanomaterials for photocatalytic degradation of organic pollutants - Awais Ahmad; Arsh e Noor; Aneela Anwar; Saadat Majeed; Safia Khan; Zaib Ul Nisa; Shafaqat Ali; Lalitha Gnanasekaran; Saravanan Rajendran; Hu Li (Environmental Research, 2024)

Evaluating soil quality and carbon storage in Western Ghats Forests, Karnataka, India, for sustainable forest management - Kaushik Saha; K. S. Anil Kumar; K. M. Nair; M. Lalitha; Parinita Das; S. P. Maske; P. James Jacob; M. D. Jessy; K. S. Karthika; V. Ramamurthy; N. G. Patil (Environmental Monitoring and Assessment, 2024)

Mitigation of heavy metal toxicity in pigeon pea by plant growth promoting Pseudomonas alcaliphila strain PAS1 isolated from contaminated environment - Chinnadurai Sathya; Natchimuthu Karmegam; Sundaram Lalitha (Environmental Geochemistry and Health, 2024)

Recent advancements in nanotechnological approaches for pollution monitoring and environmental sustainability - J. Manjunathan; M. Revathi; H. Sowmya; S. S. Meenambiga; R. Sudha; B. Prakash; Senthilkumar Nangan; Lalitha Gnanasekaran; N. Thirumalaivasan (Clean Technologies and Environmental Policy, 2024)

Photodegrading rhodamine B dye with cobalt ferrite-graphitic carbon nitride (CoFe2O4/g-C3N4) composite - Shanmugapriya Dharani; Lalitha Gnanasekaran; SaravanaVadivu Arunachalam; Anna Zielińska-Jure; Hesham S. Almoallim; Matias Soto-Moscoso (Environmental Research, 2024)

Coastal aquatic pollutants degradation using ZnCo2O4 nanorods - Lalitha Gnanasekaran; Gomathi Ramalingam; R. Suresh; Senthilkumar Nangan; Anna Zielińska-Jurek; Wei-Hsin Chen; Matias Soto-Moscoso (Environmental Research, 2024)

Promoting Agricultural Sustainability in Semi-arid Regions: An Integrated GIS–AHP Assessment of Land Suitability for Encouraging Crop Diversification - B. Kalaiselvi; M. Lalitha; Ranabir Chakraborty; S. Dharumarajan; R. Srinivasan; V. Ramamurthy; K. Karunya Lakshmi; Rajendra Hegde; K. V. Archana (Journal of the Indian Society of Remote Sensing, 2024)

Protective effect of 5,4'-dihydroxy-6,8-dimethoxy7-O-rhamnosylflavone from Indigofera aspalathoides Vahl on lipopolysaccharide-induced intestinal injury in mice - Abdullah M. AlZahrani; Peramaiyan Rajendran; Gamal M. Bekhet; Rajkapoor Balasubramanian; Lalitha Keddal Govindaram; Emad A. Ahmed; Hamza Hanieh (Inflammopharmacology, 2024)

Pedogenic variables with color indices of rubified Alfisols in the Kakalachinte microwatershed, Karnataka, South India - Gizachew Ayalew Tiruneh; Ashok Hanjagi; Bhaskara Phaneendra; M. Lalitha; R. Vasundhara; V. Ramamurty; S. Abdul Rahaman; T. Ravikiran; Agmas Amare Simegn; Tewodros Mulu Addis; Derege Tsegaye Meshesha; Tiringo Yilak Alemayehu; et al. (Geoderma Regional, 2024)

Microplastics in marine ecosystems: A comprehensive review of biological and ecological implications and its mitigation approach using nanotechnology for the sustainable environment - Eswar Marcharla; Saranya Vinayagam; Lalitha Gnanasekaran; Matias Soto-Moscoso; Wei-Hsin Chen; Sundaram Thanigaivel; Swamynathan Ganesan (Environmental Research, 2024)

Cost-effective multiplex PCR assay for simultaneous detection of bacterial leaf blight, blast and brown planthopper resistance genes in rice - Priyanka Manne; Raghavendra Rao Sanagala; Yashwanth Balmooru; Lalitha Shanti Marella; Sai Murali Raj Menon; Venkata RamanaRao Gantla; Kethavath Srinivas Naik (Journal of Plant Biochemistry and Biotechnology, 2024)

Efficiency and mechanistic insights of photocatalytic decomposition of tetracycline and rhodamine B utilizing Z-scheme g-C3N4/SnWO4 heterostructures under visible light irradiation - Ramu Boddepalli; Thirumala Rao Gurugubelli; Pammi S.V.N; V.S. Bhagavan Netheti; S. Yusub; Mohan Rao Tamtam; Ravindranadh Koutavarapu; Lalitha Saranya Pidaparthy (Environmental Research, 2024)

Rational coupling of selective electrochemical oxidation and reduction reactions for in-situ value-added chemical generation - AngelaaLincy MariaJoseph; Senthilkumar Nangan; Deepak Verma; Lalitha Gnanasekaran; Saravanan Rajendran; Thirumalaivasan Natesan; Prasit Pattananuwat; Manunya Okhawilai (Fuel, 2024)

Microbiota and Gut–Liver Axis: An Unbreakable Bond? - Saraswathy Sivaprasadan; K. N. Anila; Krishnanunni Nair; Shweta Mallick; Lalitha Biswas; Arun Valsan; Raaj Kumar Praseedom; Bipin Kumar G. Nair; Surendran Sudhindran (Current Microbiology, 2024)

Quantification and mapping of the carbon sequestration potential of soils via a quantile regression forest model - Subramanian Dharumarajan; Ramakrisnappa Vasundhara; Beeman Kalaiselvi; Manickam Lalitha; M. Rameshan; Ramasamy Srinivasan; Kavukattu Sreekumar Karthika; Kumari Sweta; Kokkuvayil Sankaranarayanan Anil Kumar; Rajendra Hegde (Earth Science Informatics, 2024)

Converting waste PET plastic into sulfonated carbon nanosheets supported PANI nanocomposite as anode catalyst in biophotovoltaic cells - Karthikeyan Chandrasekaran; Senthilkumar Nangan; Manunya Okhawilai; Lalitha Gnanasekaran; Saleh H. Salmen; Sulaiman Ali Alharbi; Hiroshi Uyama (Fuel, 2024)

Enhancing antibacterial efficacy and accelerating infectious wound healing in rats using biogenic metal nanoparticles from marine Bacillus subtilis - Raghuveer Varma Pemmadi; Nabil Abdulhafiz Alhakamy; Hani Z. Asfour; Sabna Kotta; Mohamed A. Alfaleh; Prasad Sunnapu; Ilyas Uk; Lalitha Pottail; Akhila Chithambharan; Dhanapal Yogananthan; Samuel Thavamani B; Shilpa Valiyaparambil; et al. (Frontiers in Marine Science, 2024)
Introduction Microorganisms originating from the marine environment, such as bacteria, fungi, and algae, are deliberately employed in the production of nanoparticles on account of the wide array of bioactive compounds they produce. Methods Cell-free aqueous extracts of marine Bacillus subtilis (CBPPR1) were used to synthesise AuNPs (CBPPR1AuNPs) and AgNPs (CBPPR1AgNPs). Zetasizer Nano ZS (Malvern Instruments) zeta size and zeta potential, field emission and transmission scanning electron microscopy (FE-SEM and HR-TEM), UV-visible (UV-Vis), X-ray diffraction (XRD), Fourier transform infrared (FT-IR), and EDAX were used to characterize biogenically synthesized nanoparticles (NPs). Their antibacterial activities against Escherichia coli , Klebsiella pneumoniae , and Staphylococcus aureus were investigated. The anticancer efficacy of CBPPR1Au and AgNPs was investigated in human colorectal adenocarcinoma cell lines (HT-29, HT-116). CBPPR1AgNPs formulation was studied in vitro and in-vivo rat models. The assessment focused on its efficacy in wound healing and antibacterial capabilities, comparing them against a commercial product. To determine the effectiveness of CBPPR1AgNPs in wound healing, a cutaneous wound model was employed, which included infection with S. aureus . Results and discusion CBPPR1Au and AgNPs significantly inhibited the growth of S aureus at MIC of 125 µg (CBPPR1AuNPs) and 62.5 µg (CBPPR1AgNPs) respectively. FE-SEM and HR-TEM observations confirmed that NPs caused bacterial cell leakage, damage, and shrinkage. Cancer cell viability was reduced upon treatment with increasing concentrations of CBPPR1Au and AgNPs, and apoptosis was increased in cells treated with CBPPR1Au and AgNPs relative to untreated cells (p < 0.001). CBPPR1Au and AgNPs showed significant cytotoxic activity against HT-29 (15.5 M) and HT-116 (62.5 M) cells. In-vivo experiments on rats showed minimal pus formation in groups CBPPR1AgNPs (62.5 µg/ml) G2, CBPPR1AgNPs (125 µg/ml) G3, and silver sulfadiazine G4, indicating the effective control of infections. CBPPR1AgNPs-treated wounds showed complete closure, whereas untreated G1 wounds remained unhealed. Histopathological analysis showed no adverse effects of CBPPR1AgNPs on kidneys and livers of rats. These findings suggest that CBPPR1AgNPs play a pivotal role in wound healing because of their potent antibacterial properties.

Effect of landforms and vegetations on pedological variability and crop yield along the toposequence of Eastern Coastal Plain of Odisha, India - Srinivasan Ramasamy; Lalitha Manickam; Shelton Padua; Tejashvini Ashwathappa; Jagdish Prasad; Surendra Kumar Singh (Journal of Coastal Conservation, 2024)

Biomass and waste derived silica, activated carbon and ammonia-based materials for energy-related applications – A review - Gomathi Ramalingam; A.K. Priya; Lalitha Gnanasekaran; Saravanan Rajendran; Tuan K.A. Hoang (Fuel, 2024)

RETRACTED: Environmental fate of aquatic pollutants and their mitigation by phycoremediation for the clean and sustainable environment: A review - S. Thanigaivel; Saranya Vinayagam; Lalitha Gnanasekaran; R. Suresh; Matias Soto-Moscoso; Wei-Hsin Chen (Environmental Research, 2024)

A Study of Small Molecule-Based Rhodamine-Derived Chemosensors and their Implications in Environmental and Biological Systems from 2012 to 2021: Latest Advancement and Future Prospects - Raguraman Lalitha; Sivan Velmathi (Journal of Fluorescence, 2024)

Harvesting visible light for enhanced catalytic degradation of wastewater using TiO2@Fe3O4 embedded on two dimensional reduced graphene oxide nanosheets - Saravanan Rajendran; Adriana Blanco; Lalitha Gnanasekaran; A.A. Jalil; Wei-Hsin Chen; F. Gracia (Chemosphere, 2023)

Nanosized core-shell (NiFe2O4/TiO2) heterostructure for enhanced photodegradation against polycyclic aromatic hydrocarbons - Sultan Alomairy; Lalitha Gnanasekaran; Saravanan Rajendran; Walaa F. Alsanie (Chemosphere, 2023)

Biomass waste as an alternative source of carbon and silicon-based absorbents for CO2 capturing application - R. Suresh; Lalitha Gnanasekaran; Saravanan Rajendran; A.A. Jalil; Matias Soto-Moscoso; Kuan Shiong Khoo; Zengling Ma; Heli Siti Halimatul Munawaroh; Pau Loke Show (Chemosphere, 2023)

Multifunctional natural derived carbon quantum dots from Withania somnifera (L.) – Antiviral activities against SARS-CoV-2 pseudoviron - Akhila Nair; Kanagaraj Kuppusamy; Senthilkumar Nangan; Thirumalaivasan Natesan; Jozef T. Haponiuk; Sabu Thomas; Ramasamy Ramasubburayan; Lalitha Gnanasekaran; Manickam Selvaraj; Sreeraj Gopi (Environmental Research, 2023)

Biochar supported nano core-shell (TiO2/CoFe2O4) for wastewater treatment - Sultan Alomairy; Lalitha Gnanasekaran; Saravanan Rajendran; Walaa F. Alsanie (Environmental Research, 2023)

Smart and sensitive nanomaterial-based electrochemical sensor for the determination of a poly (ADP-ribose) polymerase (PARP) inhibitor anticancer agent - Nevin Erk; Özgül Vural; Wiem Bouali; Asena Ayse Genc; Lalitha Gnanasekaran; Hassan Karimi-Maleh (Environmental Research, 2023)

Detection of microRNAs expression signatures in vitreous humor of intraocular tuberculosis - Swathi Chadalawada; SR Rathinam; Prajna Lalitha; Naresh Babu Kannan; Bharanidharan Devarajan (Molecular Biology Reports, 2023)

The degradation of bisphenol-A organic pollutant using the dispersal of TiO2 nanorods onto the partial reduction of graphene oxide nanosheets - Sultan Alomairy; Lalitha Gnanasekaran; Saravanan Rajendran; Walaa F. Alsanie (Chemosphere, 2023)

Mesoporous NiO/Ni2O3 nanoflowers for favorable visible light photocatalytic degradation of 4-chlorophenol - Lalitha Gnanasekaran; Devaraj Manoj; Saravanan Rajendran; F. Gracia; A.A. Jalil; Wei-Hsin Chen; Matias Soto-Moscoso; M.A. Gracia-Pinilla (Environmental Research, 2023)

S-scheme heterojunction photocatalysts for hydrogen production: Current progress and future prospects - Shanmugapriya Dharani; Sethumathavan Vadivel; Lalitha Gnanasekaran; Saravanan Rajendran (Fuel, 2023)

Doped nanomaterials: Application in hydrogen production via photocatalytic water splitting - R. Suresh; Lalitha Gnanasekaran; Saravanan Rajendran; Matias Soto-Moscoso (Fuel, 2023)

Development and validation of isothermal polymerase spiral reaction assay for the specific authentication of goat (Capra hircus) meat - B. Lalitha Shree; P.S. Girish; Nagappa Karabasanavar; S. Sai Reddy; Vinod Kumar Basode; D. Priyanka; P. Sankeerthi; J. Vasanthi (Food Control, 2023)

Optimization of the process parameters of catalytic plastic pyrolysis for oil production using design of experiment approaches: A review - Wei-Hsin Chen; Partha Pratim Biswas; Eilhann E. Kwon; Young-Kwon Park; Saravanan Rajendran; Lalitha Gnanasekaran; Jo-Shu Chang (Chemical Engineering Journal, 2023)

Geospatial approach for assessment of groundwater quality - Arvind Sharadchandra Gauns; Nagarajan Madasamy; R. Lalitha; Baskar Murugaiyan (Natural Hazards, 2023)

Insights of microalgae-based aquaculture feed: A review on circular bioeconomy and perspectives - Pei En Tham; Hooi Ren Lim; Kuan Shiong Khoo; Kit Wayne Chew; Yee Jiun Yap; Heli Siti Halimatul Munawaroh; Zengling Ma; Saravanan Rajendran; Lalitha Gnanasekaran; Pau Loke Show (Algal Research, 2023)

RETRACTED: Modified poly(vinylidene fluoride) nanomembranes for dye removal from water – A review - R. Suresh; Saravanan Rajendran; Lalitha Gnanasekaran; Pau Loke Show; Wei-Hsin Chen; Matias Soto-Moscoso (Chemosphere, 2023)

RETRACTED: Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2023)

Selective removal of copper (II) ions from aqueous solution using pyridyl-bridged mesoporous organosilica hybrid adsorbent - Kokila Thirupathi; Subramani Rajesh; Santhamoorthy Madhappan; Lalitha Gnanasekaran; Loganathan Guganathan; Thi Tuong Vy Phan; Seong-Cheol Kim (Environmental Research, 2023)

Association between dietary 3-monochloropropane-1,2-diol esters (3-MCPDE) and renal cancer in Peninsular Malaysia: exposure assessment and matched case-control study - Siti Hajar Muhamad Rosli; Mei Siu Lau; Tasnim Khalid; Siti Khuzaimah Maarof; Suganthi Jeyabalan; Syazwani Sirdar Ali; Norhayati Mustafa Khalid; Mohd Fairulnizal Md Noh; Ruhaya Salleh; Lalitha Palaniveloo; Mohamad Hasnan Ahmad; Nurul Izzah Ahmad; et al. (Food Additives & Contaminants: Part A, 2023)

A mechanothermal approach for the synthesis of Fe3O4 nanoparticles as dopant on mesoporous TiO2 for electrochemical determination of catechol - Devaraj Manoj; Lalitha Gnanasekaran; Saravanan Rajendran; A.A. Jalil; Mohammad Nahid Siddiqui; F. Gracia; Matias Soto-Moscoso (Environmental Research, 2023)

Nanotechnology for improved production of algal biofuels: a review - S. Thanigaivel; Saravanan Rajendran; Lalitha Gnanasekaran; Kit Wayne Chew; Dang Thuan Tran; Hoang-Dung Tran; Nguyen Khoi Nghia; Pau Loke Show (Environmental Chemistry Letters, 2023)

Deciphering the isoprenoid pigment sequestration in silkworms and its function - Hridya Hemachandran; Sankari Mohan; Ramamoorthy Siva; Lopamudra Guha; Lalitha Natarajan (International Journal of Tropical Insect Science, 2023)

Soil order knowledge as a driver in soil properties estimation from Vis-NIR spectral data – Case study from northern Karnataka (India) - S. Dharumarajan; C. Gomez; M. Lalitha; B. Kalaiselvi; R. Vasundhara; R. Hegde (Geoderma Regional, 2023)

Information seeking about genetically modified foods: readability of online information - Lalitha Samuel; Sawyer I. Basch; Joseph Fera (Journal of Consumer Protection and Food Safety, 2023)

Facile synthesis of CuO/g-C3N4 nanolayer composites with superior catalytic reductive degradation behavior - R. Suresh; N.S. Karthikeyan; Lalitha Gnanasekaran; Saravanan Rajendran; Matias Soto-Moscoso (Chemosphere, 2023)

Enhanced hydrogen adsorption properties of mesoporous nano-TiO2@SnO2 - Saravanan Rajendran; Lalitha Gnanasekaran; Tuan K.A. Hoang; D.E. Diaz-Droguett; F. Gracia; M.A. Gracia-Pinilla (Fuel, 2023)

Lipid bioproduction through optimization of thermal diluted acid pretreatment on native grass using Yarrowia lipolytica - Polinati Satya Sagar; Satish Kommoji; Iyyappan Jayaraj; Deepanraj Balakrishnan; Feroz Shaik; Mahendra Vucha; Lalitha Gnanasekaran (Fuel, 2023)

A review on S-scheme and dual S-scheme heterojunctions for photocatalytic hydrogen evolution, water detoxification and CO2 reduction - Amit Kumar; Atul Khosla; Sunil Kumar Sharma; Pooja Dhiman; Gaurav Sharma; Lalitha Gnanasekaran; Mu. Naushad; Florian J. Stadler (Fuel, 2023)

Progressive yield of nickel cobaltite nanocubes for visible light utilization and degrading activities of methyl orange dye pollutant - Lalitha Gnanasekaran; R. Suresh; Saravanan Rajendran; Wei-Hsin Chen; Matias Soto-Moscoso (Environmental Research, 2023)

Nanocubic copper cobaltite for methyl orange degradation through photocatalytic process - Lalitha Gnanasekaran; D. Shanmugapriya; V. Sasikala; Sethumathavan Vadivel; Wei-Hsin Chen; M. Arthi; Matias Soto-Moscoso (Chemosphere, 2023)

The conversion of biomass to fuels via cutting-edge technologies: Explorations from natural utilization systems - Lalitha Gnanasekaran; A.K. Priya; S. Thanigaivel; Tuan K.A. Hoang; Matias Soto-Moscoso (Fuel, 2023)

Lost in print: difficulty in reading online information pertaining to phenylketonuria - Lalitha Samuel; Joseph Fera; Corey H. Basch (Journal of Community Genetics, 2022)

Whole genome sequencing of ASD 16 and ADT 43 to identify predominant grain size and starch associated alleles in rice - Jayakanthan Mannu; Abillasha Mohan Latha; Shalini Rajagopal; Hari Dharani A. Lalitha; Raveendran Muthurajan; Arul Loganathan; Mohankumar Subbarayalu; Gnanam Ramasamy; Ramalingam Jegadeesan (Molecular Biology Reports, 2022)

Biogenic synthesis of ZnO nanoparticles mediated from Borassus flabellifer (Linn): antioxidant, antimicrobial activity against clinical pathogens, and photocatalytic degradation activity with molecular modeling - Dharman Kalaimurugan; Kandhasamy Lalitha; Kaliannan Durairaj; Palaniappan Sivasankar; Sungkwon Park; Kannan Nithya; Muthugoundar Subramanian Shivakumar; Wen-Chao Liu; Balasubramanian Balamuralikrishnan; Srinivasan Venkatesan (Environmental Science and Pollution Research, 2022)

Direct-to-consumer genetic testing in the news: a descriptive analysis - Corey H. Basch; Grace C. Hillyer; Lalitha Samuel; Erela Datuowei; Betty Cohn (Journal of Community Genetics, 2022)

An insight into phytic acid biosynthesis and its reduction strategies to improve mineral bioavailability - Sandhya Sharma; Lalitha Hari Dharani AnandKumar; Anshika Tyagi; Mehanthan Muthumilarasan; Kuldeep Kumar; Kishor Gaikwad (The Nucleus, 2022)

Biosynthesis and characterization of silver nanoparticles from symbiotic bacteria Xenorhabdus nematophila and testing its insecticidal efficacy on Spodoptera litura larvae - Kandhasamy Lalitha; Kannan Nithya; Srinivasan Venkatesan; Muthugounder Subramanian Shivakumar (BioMetals, 2022)

Soil Fertility Evaluation in Rainfed Regions of Different Agro-Climatic Zones of Karnataka, India - Lalitha. M; Rajendra Hegde; Dharumarajan. S; Arti Koyal (Agricultural Research, 2022)

Experimental Investigation of the Anisotropic Mechanical Response of the Porcine Thoracic Aorta - Manoj Myneni; Raghuveer Lalitha Sridhar; Kumbakonam R. Rajagopal; Chandler C. Benjamin (Annals of Biomedical Engineering, 2022)

Evaluation of digital soil mapping approach for predicting soil fertility parameters—a case study from Karnataka Plateau, India - Subramanian Dharumarajan; Manickam Lalitha; KV Niranjana; Rajendra Hegde (Arabian Journal of Geosciences, 2022)

Modeling neurodegenerative diseases with cerebral organoids and other three-dimensional culture systems: focus on Alzheimer’s disease - Lalitha Venkataraman; Summer R. Fair; Craig A. McElroy; Mark E. Hester; Hongjun Fu (Stem Cell Reviews and Reports, 2022)

Dysregulated expression of microRNAs in aqueous humor from intraocular tuberculosis patients - Swathi Chadalawada; Kandasamy Kathirvel; Prajna Lalitha; S. R. Rathinam; Bharanidharan Devarajan (Molecular Biology Reports, 2022)

Spatial prediction of soil depth using environmental covariates by quantile regression forest model - M. Lalitha; S. Dharumarajan; Amar Suputhra; B. Kalaiselvi; Rajendra Hegde; RS. Reddy; CR. Shiva Prasad; CS. Harindranath; BS. Dwivedi (Environmental Monitoring and Assessment, 2021)

Stream corridor encroachment and its consequences: the case of Pinga Oya tributary in the upper Mahaweli River in Sri Lanka - Lalitha Dissanayake (Modeling Earth Systems and Environment, 2021)

Hydrochemical characterization and groundwater quality in Cauvery deltaic fluvial plains of Southern India - Manickam Lalitha; Subramanian Dharumarajan; Beeman Kalaiselvi; Khandal Shivanand; Arti Koyal; Seenipandi Kaliraj; Rajendra Hegde (Environmental Science and Pollution Research, 2021)

Pharmacokinetic and pharmacodynamic evaluation of nasal liposome and nanoparticle based rivastigmine formulations in acute and chronic models of Alzheimer’s disease - Sampath Kumar L. Rompicherla; Karthik Arumugam; Sree Lalitha Bojja; Nitesh Kumar; C. Mallikarjuna Rao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
With the increasing aging population and progressive nature of the disease, Alzheimer’s disease (AD) poses to be an oncoming epidemic with limited therapeutic strategies. It is characterized by memory loss, behavioral instability, impaired cognitive function, predominantly, cognitive inability manifested due to the accumulation of β-amyloid, with malfunctioned cholinergic system. Rivastigmine, a reversible dual cholinesterase inhibitor, is a more tolerable and widely used choice of drug for AD. However, rivastigmine being hydrophilic and undergoing the first-pass metabolism exhibits low CNS bioavailability. Nanoformulations including liposomes and PLGA nanoparticles can encapsulate hydrophilic drugs and deliver them efficiently to the brain. Besides, the nasal route is receiving considerable attention recently, due to its direct access to the brain. Therefore, the present study attempts to evaluate the pharmacokinetic and pharmacodynamic properties of nasal liposomal and PLGA nanoparticle formulations of rivastigmine in acute scopolamine-induced amnesia and chronic colchicine induced cognitive dysfunction animal models, and validate the best formulation by employing pharmacokinetic and pharmacodynamic (PK-PD) modeling. Nasal liposomal rivastigmine formulation showed the best pharmacokinetic features with rapid onset of action (Tmax = 5 min), higher Cmax (1489.5 ± 620.71), enhanced systemic bioavailability ( F = 118.65 ± 23.54; AUC = 35,921.75 ± 9559.46), increased half-life (30.92 ± 8.38 min), and reduced clearance rate (Kel (1/min) = 0.0224 ± 0.006) compared to oral rivastigmine (Tmax = 15 min; Cmax = 56.29 ± 27.05; F = 4.39 ± 1.82; AUC = 1663.79 ± 813.54; t1/2 = 13.48 ± 5.79; Kel (1/min) = 0.0514 ± 0.023). Further, the liposomal formulation significantly rescued the memory deficit induced by scopolamine as well as colchicine superior to other formulations as assessed in Morris water maze and passive avoidance tasks. PK-PD modeling demonstrated a strong correlation between the pharmacokinetic parameters and acetylcholinesterase inhibition of liposomal formulation.

Predicting and Mapping of Soil Hydraulic Properties in Karnataka - S. Dharumarajan; Rajendra Hegde; M. Lalitha; R. Vasundhara (Journal of the Indian Society of Remote Sensing, 2021)

Modeling and Mapping of Salt-Affected Soils through Spectral Indices in Inland Plains of Semi-arid Agro-Ecological Region - Lalitha Manickam; Dharumarajan Subramanian; Shivanand Khandal; Rajendra Hegde (Journal of the Indian Society of Remote Sensing, 2021)

Bioinspired Gold Nanoparticle Synthesis Using Terminalia bellerica Fruit Parts and Exploring Their Anti‐bacterial Potency In Vitro - Akhila Chithambharan; Lalitha Pottail; Rekha Manjunath Mirle; Ravimoorthy Rajalakshmi; Aruna Ponnusamy (Indian Journal of Microbiology, 2021)

Soil-landscape relationships in Vedavathi river basin, Chitradurga district, Karnataka, India: morphology and textural and chemical properties - Bhaskara phaneendra Bhaskar; Sompura chinnappa Ramesh kumar; Bidarakere puttakariyappa Lakshmikantha; Manickam Lalitha; Arati Koyal (Arabian Journal of Geosciences, 2021)

Evaluating pedogenesis and soil Atterberg limits for inducing landslides in the Western Ghats, Idukki District of Kerala, South India - M. Lalitha; K. S. Anil Kumar; K. M. Nair; S. Dharumarajan; Arti Koyal; Shivanand Khandal; S. Kaliraj; Rajendra Hegde (Natural Hazards, 2021)

Modeling Seasonal Variation in Urban Weather in Sub-Tropical Region of Delhi - Kshama Gupta; Pushplata; Allaka Lalitha; Payel Ghosh Dastidar; Jillela Malleswara Rao; Praveen Thakur; Jai Shankar Gummapu; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2021)

Biocontrol-based management of fall armyworm, Spodoptera frugiperda (J E Smith) (Lepidoptera: Noctuidae) on Indian Maize - Richa Varshney; B. Poornesha; A. Raghavendra; Y. Lalitha; V. Apoorva; B. Ramanujam; R. Rangeshwaran; K. Subaharan; A. N. Shylesha; N. Bakthavatsalam; Malvika Chaudhary; Vinod Pandit (Journal of Plant Diseases and Protection, 2021)

Metformin ameliorates the status epilepticus- induced hippocampal pathology through possible mTOR modulation - Sree Lalitha Bojja; Bikash Medhi; Shashi Anand; Alka Bhatia; Rupa Joshi; Ranjana W. Minz (Inflammopharmacology, 2021)

Screening for novel rice sheath blight resistant germplasm and their biochemical characterization - S. Lalitha Pavani; Vineeta Singh; Sanjay Kumar Goswami; P. K. Singh (Indian Phytopathology, 2020)

Green synthesis and characterization of novel 1,2,4,5-tetrasubstituted imidazole derivatives with eco-friendly red brick clay as efficacious catalyst - Nagaraju Kerru; Lalitha Gummidi; Sandeep V. H. S. Bhaskaruni; Surya Narayana Maddila; Sreekantha B. Jonnalagadda (Molecular Diversity, 2020)

Prediction of Soil Depth in Karnataka Using Digital Soil Mapping Approach - S. Dharumarajan; R. Vasundhara; Amar Suputhra; M. Lalitha; Rajendra Hegde (Journal of the Indian Society of Remote Sensing, 2020)

Molecular and morphological discrimination of Chrysanthemum indicum using allele-specific PCR and T-shaped trichome - Suleman Abid; Lalitha Kaliraj; Muhammad Huzaifa Arif; Joon Hurh; Jong Chan Ahn; Deok Chun Yang; Seok-Kyu Jung (Molecular Biology Reports, 2020)

Estimation of soil loss by an integrated approach of USLE and geospatial techniques—a case study of Kumulur watershed - Nagarajan Madasamy; Mercy Backiyam Joshua; Lalitha Rajangam (Arabian Journal of Geosciences, 2020)

Fungal Infections of the Eye - Ram Rammohan; Vishwanathaiah Suneetha; Sagnik Sen; Gunasekaran Rameshkumar; Prajna Lalitha (Current Clinical Microbiology Reports, 2020)

Efficient synthesis of novel pyrazole-linked 1,2,4-triazolidine-3-thiones using bismuth on zirconium oxide as a recyclable catalyst in aqueous medium - Nagaraju Kerru; Sandeep V. H. S. Bhaskaruni; Lalitha Gummidi; Surya Narayana Maddila; Parvesh Singh; Sreekantha B. Jonnalagadda (Molecular Diversity, 2020)

Antimicrobial activity of metal and non-metallic nanoparticles from Cyperus rotundus root extract on infectious disease causing pathogens - Santhiya Sasidharan; Lalitha Pottail (Journal of Plant Biochemistry and Biotechnology, 2020)

Assessment of Topographical Factor (LS-Factor) Estimation Procedures in a Gently Sloping Terrain - P. R. Anjitha Krishna; R. Lalitha; K. Shanmugasundaram; M. Nagarajan (Journal of the Indian Society of Remote Sensing, 2019)

Macromolecular properties and partial amino acid sequence of a Kunitz-type protease inhibitor from okra (Abelmoschus esculentus) seeds - Debparna Datta; Gottfried Pohlentz; Saradamoni Mondal; M Bala Divya; Lalitha Guruprasad; Michael Mormann; Musti J Swamy (Journal of Biosciences, 2019)

Secondary structure of the internal transcribed rDNA (ITS) regions of Cosmopolites sordidus (Germar) and Odoiporus longicollis (Olivier): a first report in family Curculionidae - Lalitha Sunil Kumar (International Journal of Tropical Insect Science, 2019)

Formation of Biogenic Amines and Associated Biochemical and Microbial Attributes of Whole Sutchi Catfish ( Pangasianodon hypophthalmus ) during Iced Storage - S. J. Laly; Jeyakumari Annamalai; K. Ashok Kumar; T. V. Sankar; Lalitha KV; George Ninan (Journal of Aquatic Food Product Technology, 2019)

Comparative α-glucosidase and α-amylase inhibition studies of rhodanine–pyrazole conjugates and their simple rhodanine analogues - Parvesh Singh; Serisha Mothilal; Nagaraju Kerru; Ashona Singh-Pillay; Lalitha Gummidi; Ochuko L. Erukainure; Md. Shahidul Islam (Medicinal Chemistry Research, 2019)

Analyses of the internal transcribed rDNA spacers (ITS1 and ITS2) of Indian weevils of Odoiporus longicollis (Olivier) reveal gene flow between locations - Lalitha Sunil Kumar; Pallavi Shankar; Vishvas M. Kulkarni (International Journal of Tropical Insect Science, 2018)

Assessment of the hurricane-induced power outages from a demographic, socioeconomic, and transportation perspective - Mehmet Baran Ulak; Ayberk Kocatepe; Lalitha Madhavi Konila Sriram; Eren Erman Ozguven; Reza Arghandeh (Natural Hazards, 2018)

miR Cluster 143/145 Directly Targets Nrl and Regulates Rod Photoreceptor Development - Sreekumaran Sreekanth; Vazhanthodi A Rasheed; Lalitha Soundararajan; Jayesh Antony; Minakshi Saikia; Krishnankutty Chandrika Sivakumar; Ani V Das (Molecular Neurobiology, 2017)

Genetic variability in Indian populations of banana corm weevil [Cosmopolites sordidus (Coleoptera: Curculionidae)] assessed by RAPDs and AFLPs - Sweta Kumari U. Yadav; Jyotsna Singh; B. Padmanaban; Lalitha Sunil Kumar (International Journal of Tropical Insect Science, 2017)

In Silico Drug-Designing Studies on Flavanoids as Anticolon Cancer Agents: Pharmacophore Mapping, Molecular Docking, and Monte Carlo Method-Based QSAR Modeling - Lalitha Simon; Abdelli Imane; K. K. Srinivasan; Lokesh Pathak; I. Daoud (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Antioxidant, anticancer and electrochemical redox properties of new bis(2,3-dihydroquinazolin-4(1H)-one) derivatives - Paramasivam Sivaguru; Kandasamy Parameswaran; Appaswami Lalitha (Molecular Diversity, 2017)

Clinical Translation of the National Institutes of Health’s Investments in Nanodrug Products and Devices - Lori A. Henderson; Lalitha K. Shankar (The AAPS Journal, 2017)

Methodological approach for the collection and simultaneous estimation of greenhouse gases emission from aquaculture ponds - Muthuraman Vasanth; Moturi Muralidhar; Ramamoorthy Saraswathy; Arunachalam Nagavel; Jagabattula Syama Dayal; Marappan Jayanthi; Natarajan Lalitha; Periyamuthu Kumararaja; Koyadan Kizhakkedath Vijayan (Environmental Monitoring and Assessment, 2016)

Soil carbon fractions influenced by temperature sensitivity and land use management - M. Lalitha; Praveen Kumar (Agroforestry Systems, 2016)

Cryopreservation of adult primate testes - Lavanya Pothana; Naresh Kumar Venna; Lalitha Devi; Anju Singh; Ipsita Chatterjee; Sandeep Goel (European Journal of Wildlife Research, 2016)

Earthen levee slide detection via automated analysis of synthetic aperture radar imagery - Lalitha Dabbiru; James V. Aanstoos; Nicolas H. Younan (Landslides, 2016)

Anticancer potential of pyrrole (1, 2, a) pyrazine 1, 4, dione, hexahydro 3-(2-methyl propyl) (PPDHMP) extracted from a new marine bacterium, Staphylococcus sp. strain MB30 - P. Lalitha; V. Veena; P. Vidhyapriya; Pragna Lakshmi; R. Krishna; N. Sakthivel (Apoptosis, 2016)

Streptomyces lonarensis sp. nov., isolated from Lonar Lake, a meteorite salt water lake in India - Trupti K. Sharma; Rahul Mawlankar; Vidya V. Sonalkar; Vidhya K. Shinde; Jing Zhan; Wen-Jun Li; Meenakshi V. Rele; Syed G. Dastager; Lalitha Sunil Kumar (Antonie van Leeuwenhoek, 2016)

Influence of Freeze-Dried Shrimp Meat in Pasta Processing Qualities of Indian T. durum Wheat - N. S. Ramya; P. Prabhasankar; Lalitha R. Gowda; V. K. Modi; N. Bhaskar (Journal of Aquatic Food Product Technology, 2015)

Male biased gene flow in banana pseudostem weevil (Odoiporus longicollis Oliver) as revealed by analysis of the COI-tRNALeu COII region - Pallavi Shankar; Vishvas M. Kulkarni; Lalitha Sunil Kumar (Genetica, 2015)

Hematological and Biochemical Parameters in Apparently Healthy Indian Population: Defining Reference Intervals - Shrilekha Sairam; Suhasini Domalapalli; Sundaram Muthu; Jayanthi Swaminathan; Vivek A. Ramesh; Lalitha Sekhar; Palak Pandeya; Udhaya Balasubramaniam (Indian Journal of Clinical Biochemistry, 2014)

Cloning and Sequence Analysis of Three Variants of the Gene Encoding Alkaline Xylanase C from the Alkaliphilic Bacillus sp. (NCL 87-6-10) - Poonam Sharma; Meenakshi V. Rele; Lalitha Sunil Kumar (Biochemical Genetics, 2013)

Ligand-based drug design for human endothelin converting enzyme-1 inhibitors - Karunakar Tanneeru; Itishri Sahu; Lalitha Guruprasad (Medicinal Chemistry Research, 2013)

Making an Indian traditional rice variety Mahsuri, bacterial blight resistant using marker-assisted selection - Lalitha Devi Guvvala; Pranitha Koradi; Vinay Shenoy; Lalitha Shanti Marella (Journal of Crop Science and Biotechnology, 2013)

Protective Effect of Neferine Against Isoproterenol-Induced Cardiac Toxicity - Gurusamy Lalitha; Paramasivan Poornima; Arjunan Archanah; Viswanadha Vijaya Padma (Cardiovascular Toxicology, 2013)

Aflatoxin contamination in food commodities in Bangladesh - Monika Roy; Julie Harris; Sadia Afreen; Eszter Deak; Lalitha Gade; S. Arunmozhi Balajee; Benjamin Park; Tom Chiller; Stephen Luby (Food Additives & Contaminants Part B-Surveillance, 2013)

The imidazolidone analogs as phospholipase D1 inhibitors: analysis of the three-dimensional quantitative structure–activity relationship - Srinivas Nakka; Lalitha Guruprasad (Medicinal Chemistry Research, 2012)

Three-dimensional quantitative structure–activity relationship (3D-QSAR) analysis and molecular docking of ATP-competitive triazine analogs of human mTOR inhibitors - Karunakar Tanneeru; Bandi Madhusudhan Reddy; Lalitha Guruprasad (Medicinal Chemistry Research, 2012)

Hemocompatibility of Silicon-Based Substrates for Biomedical Implant Applications - Lalitha Muthusubramaniam; Rachel Lowe; William H. Fissell; Lingyan Li; Roger E. Marchant; Tejal A. Desai; Shuvo Roy (Annals of Biomedical Engineering, 2011)

Computational approach towards promoter sequence comparison via TF mapping using a new distance measure - A. Meera; Lalitha Rangarajan; Savithri Bhat (Interdisciplinary Sciences: Computational Life Sciences, 2011)

Neuronal vs. Glial Fate of Embryonic Stem Cell-Derived Neural Progenitors (ES-NPs) is Determined by FGF2/EGF During Proliferation - Rajendran Sanalkumar; Sasidharan Vidyanand; Chandrasekharan Lalitha Indulekha; Jackson James (Journal of Molecular Neuroscience, 2010)

Assessing the antidepressant-like effects of carbetocin, an oxytocin agonist, using a modification of the forced swimming test - Stella Chaviaras; Plato Mak; David Ralph; Lalitha Krishnan; Jillian H. Broadbear (Psychopharmacology, 2010)

The unique enzymatic function of field bean (Dolichos lablab) d-galactose specific lectin: a polyphenol oxidase - Santosh R. Kanade; Devavratha H. Rao; Ramanath N. Hegde; Lalitha R. Gowda (Glycoconjugate Journal, 2009)

Computational approach towards finding evolutionary distance and gene order using promoter sequences of central metabolic pathway - Meera A; Lalitha Rangarajan; Savithri Bhat (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Adeno-associated virus type 2 vectors: transduction and long-term expression in cerebellar Purkinje cells in vivo is mediated by the fibroblast growth factor receptor 1 - Lalitha R. Belur; William F. Kaemmerer; R. Scott McIvor; Walter C. Low (Archives of Virology, 2008)

Mimosine Mitigates Oxidative Stress in Selenium Deficient Seedlings of Vigna radiata. Part II: Mitochondrial Uptake of 75Selenium and Mimosine - K. Lalitha; S. R. Kulothungan (Biological Trace Element Research, 2007)

Mimosine Mitigates Oxidative Stress in Selenium Deficient Seedlings of Vigna radiata-Part I: Restoration of Mitochondrial Function - K. Lalitha; S. Rajendra Kulothungan (Biological Trace Element Research, 2007)

Cytotoxic activity of flavone glycoside from the stem of Indigofera aspalathoides Vahl - Rajkapoor Balasubramanian; Murugesh Narayanan; Lalitha Kedalgovindaram; Krishna Devarakonda Rama (Journal of Natural Medicines, 2006)

Extracellular β-agarase LSL-1 producing neoagarobiose from a newly isolated agar-liquefying soil bacterium, Acinetobacter sp., AG LSL-1 - M. Lakshmikanth; S. Manohar; Y. Souche; J. Lalitha (World Journal of Microbiology and Biotechnology, 2006)

Optimization of Culture Conditions for the Production of Extracellular Agarases from Newly Isolated Pseudomonas Aeruginosa AG LSL-11 - M. Lakshmikanth; S. Manohar; J. Patnakar; P. Vaishampayan; Y. Shouche; J. Lalitha (World Journal of Microbiology and Biotechnology, 2006)

Metabolic characteristics of an aerobe isolated from a methylotrophic methanogenic enrichment culture - Stephen V. Rapheal; K. R. Swaminathan; K. Lalitha (Journal of Biosciences, 2003)

Sequence analysis corresponding to the PPE and PE proteins inMycobacterium tuberculosis and other genomes - Swathi Adindla; Lalitha Guruprasad (Journal of Biosciences, 2003)

Screening for homozygosity by descent in families with autosomal recessive retinitis pigmentosa - Kota Lalitha; Subhadra Jalali; Tejas Kadakia; Chitra Kannabiran (Journal of Genetics, 2002)

In Vitro Characterization of Hepatic Flavopiridol Metabolism Using Human Liver Microsomes and Recombinant UGT Enzymes - Jacqueline Ramírez; Lalitha Iyer; Kim Journault; Patrick Bélanger; Federico Innocenti; Mark J. Ratain; Chantal Guillemette (Pharmaceutical Research, 2002)

Comparative Analysis of Genetic Diversity Among Indian Populations of Scirpophaga incertulas by ISSR-PCR and RAPD-PCR - Lalitha Sunil Kumar; Arun S. Sawant; Vidya S. Gupta; Prabhakar K. Ranjekar (Biochemical Genetics, 2001)

Use of DNA Markers in Prediction of Hybrid Performance and Heterosis for a Three-Line Hybrid System in Rice - S. P. Joshi; S. G. Bhave; K. V. Chowdari; G. S. Apte; B. L. Dhonukshe; K. Lalitha; P. K. Ranjekar; V. S. Gupta (Biochemical Genetics, 2001)

Genetic Variation in Indian Populations of Scirpophaga incertulas as Revealed by RAPD-PCR Analysis - Lalitha Sunil Kumar; Arun S. Sawant; Vidya S. Gupta; Prabhakar K. Ranjekar (Biochemical Genetics, 2001)

Oxidative stress during selenium deficiency in seedlings oftrigonella foenum-graecum and mitigation by mimosine - M. Sreekala; T. R. Santosh; K. Lalitha (Biological Trace Element Research, 1999)

Oxidative stress during selenium deficiency in seedlings ofTrigonella foenum-graecum and mitigation by mimosine part II. glutathione metabolism - T. R. Santosh; M. Sreekala; K. Lalitha (Biological Trace Element Research, 1999)

Selenium-mediated differential response of β-glucosidase and β-galactosidase of germinatingTrigonella foenum-graecum - M. Sreekala; K. Lalitha (Biological Trace Element Research, 1998)

Studies on simultaneous inhibition of trypsin and chymotrypsin by horsegram Bowman-Birk inhibitor - Balaji Prakash; M. R. N. Murthy; Y. N. Sreerama; D. Rajagopal Rao; Lalitha R. Gowda (Journal of Biosciences, 1997)

Immunodiagnosis of human lymphatic filariasis: A review - Lalitha; P. Suba; S. Kaliraj; P. Kunthala Jayaraman; R. B. Narayanan (Indian Journal of Clinical Biochemistry, 1997)

Iron supplementation moderates but does not cure the Belgrade anemia - Michael Garrick; Donna Scott; Susannah Walpole; Eric Finkelstein; Joy Whitbred; Sandeep Chopra; Lalitha Trivikram; David Mayes; Daphne Rhodes; Kimberly Cabbagestalk; Rahmi Oklu; Adnan Sadiq; et al. (BioMetals, 1997)

Evidence for altered structure and impaired mitochondrial electron transport function in selenium deficiency - P. Rani; K. Lalitha (Biological Trace Element Research, 1996)

Mitochondrial selenium-75 uptake and regulation revealed by kinetic analysis - K. Lalitha; P. Rani (Biological Trace Element Research, 1995)

Subcellular distribution of selenium during uptake and its influence on mitochondrial oxidations in germinatingVigna radiata L - Kumaraswamy Easwari; K. Lalitha (Biological Trace Element Research, 1995)

Isolation of a novel rod shaped methanogen growing on methanol and 2-propanol - K. Lalitha; S. Krishnan (Archives of Microbiology, 1991)

Selenium-mediated biochemical changes in Japanese quails - Vasanthy Narayanaswami; K. Lalitha (Biological Trace Element Research, 1987)

Selenium-mediated biochemical changes in Japanese quails - Mary Babu; Padma Bai; Vasanthy Narayanaswami; K. Lalitha; Joseph K. Thomas (Biological Trace Element Research, 1986)

Selenium-mediated biochemical changes in Japanese quail - Vasanthy Narayanaswami; R. Padma Bai; Mary Babu; K. Lalitha (Biological Trace Element Research, 1986)

Purification and properties of laccase from Ganoderma lucidum - H. Lalitha Kumari; M. Sirsi (Archives of Microbiology, 1972)